Die Kriterien und Zusammensetzung der EU-Blacklist als Grundlage des Steueroasen-Abwehrgesetzes – Eine kritische Würdigung - Schön, Lena; Graßl, Benjamin; Giese, Henning (Steuer und Wirtschaft)

Do Country Risk Factors Attenuate the Effect of Tax Loss Incentives on Corporate Risk-Taking? - Osswald, Benjamin; Sureth-Sloane, Caren
This study investigates whether country risk factors, including political and fiscal budget risk, attenuate the effectiveness of tax policy tools that aim to encourage corporate risk-taking. Exploiting a cross-country panel, we predict and find that the effectiveness of loss offset rules and tax rate changes is fully attenuated for firms located in high-risk countries. We document the attenuating effect of country risk is more pronounced in high-tax countries or when countries increase their corporate tax rate. Additional tests around the U.S. federal budget crises from 2011 to 2013 indicate that temporarily heightened fiscal budget risk attenuates the effectiveness of loss offset rules even in countries with low political risk. We identify conditions (low political and low fiscal budget risk) under which targeted tax policy tools effectively stimulate risk-taking. This suggests that ensuring taxpayers receive tax refunds is important in times of economic crises with budgetary or political challenges.

Komplexität von Verrechnungspreisen und Tax Compliance: Einblicke in deutsche Unternehmen - Greil, Stefan; Kaluza-Thiesen, Eleonore; Schulz, Kim Alina; Sureth-Sloane, Caren (Deutsches Steuerrecht)

The conditional impact of market consolidation and market power on banking stability – Evidence from Europe - Herwald, Sarah; Voigt, Simone; Uhde, André (Journal of Risk Finance)
Purpose Academic research has intensively analyzed the relationship between market concentration or market power and banking stability but provides ambiguous results, which are summarized under the concentration-stability/fragility view. We provide empirical evidence that the mixed results are due to the difficulty of identifying reliable variables to measure concentration and market power. Design/methodology/approach Using data from 3,943 banks operating in the European Union (EU)-15 between 2013 and 2020, we employ linear regression models on panel data. Banking market concentration is measured by the Herfindahl–Hirschman Index (HHI), and market power is estimated by the product-specific Lerner Indices for the loan and deposit market, respectively. Findings Our analysis reveals a significantly stability-decreasing impact of market concentration (HHI) and a significantly stability-increasing effect of market power (Lerner Indices). In addition, we provide evidence for a weak (or even absent) empirical relationship between the (non)structural measures, challenging the validity of the structure-conduct-performance (SCP) paradigm. Our baseline findings remain robust, especially when controlling for a likely reverse causality. Originality/value Our results suggest that the HHI may reflect other factors beyond market power that influence banking stability. Thus, banking supervisors and competition authorities should investigate market concentration and market power simultaneously while considering their joint impact on banking stability.
Keywords: market concentration; market power; banking stability; European banking

Distortional effects of separate accounting and formula apportionment on factor allocation - Ortmann, Regina; Pummerer, Erich (Journal of Business Economics)
Abstract We examine distortions caused by tax base allocation systems–separate accounting (SA) or formula apportionment (FA)–with respect to the allocation of assets and workforce within multinational entities (MNEs). The effects of both systems are intensively debated by EU Member States as they are striving to implement a European tax system. Its introduction would lead to a switch from SA to FA. Moreover, Pillar One of the recent global tax reform includes a mix of both tax base allocation systems. We find that, against the claims of the EU, FA does not necessarily create lower distortions of the factor allocation. Decisive for that assessment is the level of profit shifting under SA. Our results indicate that, in tendency, the factor allocation is more severely distorted by FA when the profit shifting possibilities were rather low under SA. In contrast to former studies, we highlight the importance of analyzing the status quo under the recently applied system (SA) in order to be able to assess the consequences of a switch from SA to FA. Our results are interesting for policy-makers as they help anticipating reactions of MNEs to a change in the applied tax base allocation system and for companies as a basis for future tax planning.
Keywords: Economics and Econometrics; Business and International Management

Beste Bedingungen für junge Ökonominnen und Ökonomen? Neue Daten und Empfehlungen der Arbeitsgruppe “Nachwuchs” im Verein für Socialpolitik - Bayer, Christian; Englmaier, Florian; Riphahn, Regina; Schmidt-Dengler, Philipp; Sondergeld, Virgina; Sureth-Sloane, Caren; von Wangenheim, Jonas; Weizsäcker, Georg (Perspektiven der Wirtschaftspolitik)
Der Verein für Socialpolitik hat zur Bearbeitung seines Schwerpunktthemas „Nachwuchs“ für die Dauer der Kalenderjahre 2021-2022 eine Arbeitsgruppe eingerichtet – im Folgenden: AG Nachwuchs –, deren Aufgabe das Vorlegen eines umfassenden Berichts zur Situation der VWL-Promovierenden und -PostDocs im DACH-Raum ist. Gestützt auf Datenerhebungen und strukturierte Interviews formuliert die AG Nachwuchs in diesem Bericht zwei Empfehlungen, jeweils eine für den Doc- und den PostDoc-Bereich. Sie empfiehlt im PostDoc-Bereich, dass die Fakultäten bzw. verwandte VWL-Einrichtungen den Übergang zu Tenure-Track beschleunigen und ihn durch eine systematische Planung der Zahlenverhältnisse zwischen den Karrierestufen bei ihrem wissenschaftlichen Personal begleiten. Dadurch sollen bessere Karriereperspektiven erreicht werden. Sowohl die befragten Nachwuchskräfte als auch die befragten Professor:innen und Programmleitungen betonen die Thematik der Stellenperspektiven stark. Im Doc-Bereich dokumentieren die Erhebungsdaten eine überraschend geringe Zufriedenheit der VWL-Promovierenden mit der Betreuungssituation durch die Professorenschaft. Die AG Nachwuchs empfiehlt daher eine höhere Betreuungsdichte und eine stärkere Vernetzung von Promovierenden. Weitere Hilfestellungen für Promovierende können in Mehrfach- oder Teambetreuungen sowie in der Bereitstellung von Informationen über die Vielfalt möglicher Karrierewege bestehen.

Towards an Amended Arm´s Length Principle - Tackling Complexity and Implementing Destination Rules in Transfer Pricing - Greil, Stefan; Overesch, Michael; Rohlfing-Bastian, Anna; Schreiber, Ulrich; Sureth-Sloane, Caren (Intertax)

Zusatzkosten der Besteuerung – Eine Analyse des steuerlichen Verwaltungsaufwands und der subjektiv wahrgenommenen Steuerbelastung - Fochmann, Martin; Heinemann-Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren (Steuer und Wirtschaft)

„Allowing the Economy to Breathe Even During the Crisis“ – Interview with Tax Expert Caren Sureth-Sloane - Unterstell, Rembert (german research – Magazine of the Deutsche Forschungsgemeinschaft)

GBP-Monitor: Betriebswirtschaftliche Einschätzungen und Erwartungen von Unternehmen in Deutschland. Unternehmenstrends im November 2023 - Maiterth, Ralf; Sureth-Sloane, Caren; Dyck, Daniel; Heinemann-Heile, Vanessa

Nonfinancial Reporting and Real Sustainable Change: Relationship Status—It’s Complicated - Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Organization & Environment)
The relationship between nonfinancial reporting and real sustainable change within and beyond organizations is fraught with complication. Furthermore, all facets of the relationship have not been examined equally. The contributions of this special issue made substantive progress in this regard and draw our focus to several remaining complications—in particular, the societal impacts of nonfinancial reporting. With this introduction, we seek to move the conversation forward by proposing a framework that disentangles the linkages between nonfinancial reporting and real sustainable change at multiple levels of analysis. We highlight the distinction between sustainability-related outputs and outcomes that typically materialize at the firm level, and eventually lead to sustainable impact at the societal level. Future research should advance this distinction and scrutinize the impact of real sustainable change beyond firm-level outputs, study the organizational change processes from antecedents to impacts, and examine the interrelationships between different instruments to foster real sustainable change.
Keywords: Organizational Behavior and Human Resource Management; General Environmental Science

﻿DARC 2023 at Radboud University: Societal challenges in accounting research and education - De Meyst, Karen; Niederkofler, Thomas; Reimsbach, Daniel (Maandblad voor Accountancy en Bedrijfseconomie)
This year, the 7th edition of the Dutch Accounting Research Conference (DARC) was hosted by the Nijmegen School of Management at Radboud University on Thursday, March 23. In total, over 75 accounting researchers from various Dutch universities were welcomed by Frank Hartmann, chair of the accounting group and head of the Business Economics department. During the day, four keynote speakers presented their research and in a panel discussion, the current state of accounting education was debated. In the evening, participants gathered to network over dinner. This article presents a discussion of the theme of the conference, an outline of the research papers and projects presented during the conference, and a summary of the panel discussion on Accounting Education.
Keywords: General Arts and Humanities

2022 Global MNC Tax Complexity Survey - Harst, Simon; Schanz, Deborah; Siegel, Felix; Sureth-Sloane, Caren

Towards Green Driving - Income Taxes Incentives for Plug-In Hybrids - Giese, Henning; Holtmann, Svea

Tax Complexity, Tax Department Structure, and Tax Risk - Giese, Henning; Koch, Reinald; Sureth-Sloane, Caren

When Do Firms Highlight Their Effective Tax Rate? - Flagmeier, Vanessa; Müller, Jens; Sureth-Sloane, Caren (Accounting and Business Research)
This study examines GAAP effective tax rate (ETR) visibility as a distinct disclosure choice in firms’ financial statements. By applying a game-theory disclosure model for the voluntary disclosure strategies of firms, in a tax setting, we argue that firms face a trade-off in their ETR disclosure decisions. On the one hand, firms have an incentive to enhance their ETR disclosure when the ratio offers shareholders ‘favourable conditions’, for example, higher expected after-tax cash flows. On the other hand, the disclosure of a favourable low ETR could attract the attention of tax auditors and the public and ultimately result in disclosure costs. We empirically test disclosure behaviour by examining the relation between disclosure visibility and different ETR conditions that reflect different stakeholder-specific costs and benefits. While we find that unfavourable ETR conditions are not highlighted, we observe higher disclosure visibility for favourable ETRs (smooth, close to the industry average, and decreasing ETRs). Additional analyses reveal that this high visibility is characteristic of firm years with only moderately decreasing ETRs at usual ETR levels, while extreme ETRs are not highlighted. Interestingly and in contrast to our main results, a subsample of family firms does not seem to highlight favourable ETRs.

Losses Never Sleep – The Effect of Tax Loss Offset on Stock Market Returns during Economic Crises - Koch, Reinald; Holtmann, Svea; Giese, Henning (Journal of Business Economics)

The Tax Complexity Index – A Survey-Based Country Measure of Tax Code and Framework Complexity - Hoppe, Thomas; Schanz, Deborah; Sturm, Susann; Sureth-Sloane, Caren (European Accounting Review)

Umfrage: Tax Compliance und Verrechnungspreise - Greil, Stefan; Kaluza-Thiesen, Eleonore; Schulz, Kim Alina; Sureth-Sloane, Caren

GBP-Monitor Q3/2023: Das Wachstumschancengesetz – ein Investitionsimpuls? - Maiterth, Ralf; Sureth-Sloane, Caren; Dyck, Daniel; Heinemann-Heile, Vanessa (Schmalenbach IMPULSE)

Umfrage: Bewertung Investitionsfördernder Maßnahmen durch Unternehmen aus Handel, Dienstleistung und Industrie - Heinemann-Heile, Vanessa; Maiterth, Ralf; Sureth-Sloane, Caren

Umfrage: Beurteilung Investitionsfördernder Maßnahmen durch Unternehmen im Handwerk - Heinemann-Heile, Vanessa; Maiterth, Ralf; Sureth-Sloane, Caren

Der Wirtschaft auch in der Krise das Atmen erlauben, Pandemie und Ökonomie – Interview mit Steuerexpertin Caren Sureth-Sloane - Unterstell, Rembert (forschung - Das Magazin der Deutschen Forschungsgemeinschaft)

Der Wirtschaft auch in der Krise das Atmen erlauben, Pandemie und Ökonomie – Interview mit Steuerexpertin Caren Sureth-Sloane - Unterstell, Rembert

Allowing the Economy to Breathe Even During the Crisis – Interview with Tax Expert Caren Sureth-Sloane - Unterstell, Rembert

Turnover-Based Corporate Income Taxation and Corporate Risk-Taking - Amberger, Harald; Siahaan, Fernando; Sureth-Sloane, Caren

The conditional impact of market consolidation and market power on banking stability – Evidence from Europe - Herwald, Sarah; Voigt, Simone; Uhde, André

The dark triad and corporate sustainability: An empirical analysis of personality traits of middle managers - Pelster, Matthias; Schaltegger, Stefan (Business Ethics, the Environment & Responsibility)

Can Tax Rate Changes Accelerate Investment under Entry and Exit Flexibility? – Insights from an Economic Experiment - Fahr, René; Janssen, Elmar A.; Sureth-Sloane, Caren (FinanzArchiv / Public Finance Analysis)
This study investigates the conditions under which tax rate changes accelerate risky investments. While tax rate increases are often expected to harm investment, analytical studies find tax rate increases may foster investment under flexibility.We design a theorybased experimentwith a binomial random walk and entry–exit flexibility.We find accelerated investment upon tax rate increases irrespective of an exit option, but no corresponding response to tax cuts. This asymmetry may be due to tax salience and mechanisms from irreversible choice under uncertainty. Given this evidence of unexpected tax-reform effects, tax policymakers should carefully consider behavioral aspects.
Keywords: Economic ExperimentM; Investment Decisions; Tax Effects; Timing Flexibility; Uncertainty

How Does Trust Affect Concessionary Behavior in Tax Bargaining? - Eberhartinger, Eva; Speitmann, Raffael; Sureth-Sloane, Caren; Wu, Yuchen (FinanzArchiv / Public Finance Analysis)
We study the bargaining behavior between auditor and auditee in a tax setting and scrutinize the effect of interpersonal trust and trust in government on both parties’ concessions. We find evidence that both kinds of trust affect the concessionary behavior, albeit in different ways. While trust in government affects concessionary behavior in line with intuitive predictions, we find that interpersonal trust only affects tax auditors. For high interpersonal trust, the alleviating effect of high trust in government on tax auditors’ concessions is less pronounced. Our findings help tax authorities to shape programs to enhance compliance in an atmosphere of trust.
Keywords: Behavioral Taxation; Concessionary Behavior; Interpersonal Trust; Tax Audit; Trust in Government

Risk allocation through securitization – Evidence from non-performing loans - Wengerek, Sascha Tobias; Hippert, Benjamin; Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique and hand-collected sample of 648 true sale loan securitization transactions issued by 57 stock-listed banks across the EU-12 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the relationship between true sale loan securitization and the issuing banks’ non-performing loans to total assets ratios. Overall, we provide evidence for a negative impact of securitization on NPL exposures suggesting that banks predominantly used securitization as an instrument of credit risk transfer and diversification. In addition, the analysis at hand reveals a time-sensitive relationship between securitization and NPL exposures. While we observe an even stronger NPL-reducing effect through securitization during the non-crisis periods, the effect reverses during and after the global financial crisis suggesting that banks were forced to provide credit enhancement and employ securitization as a funding management tool. Along with the results from a variety of sensitivity analyses our study provides important implications for the recent debate on reducing NPL exposures of European banks by revitalizing the European securitization market.
Keywords: European Banking; Non-performing Loans; Securitization

Attention triggers and investors' risk-taking - Arnold, Marc; Pelster, Matthias; Subrahmanyam, Marti G. (Journal of Financial Economics)
The paper investigates the impact of individual attention on investor risk-taking. We analyze a large sample of trading records from a brokerage service that allows its customers to trade contracts-for-differences (CFD), and sends standardized push messages on recent stock performance to its client investors. The advantage of this sample is that it allows us to isolate the "push" messages as individual attention triggers, which we can directly link to the same individuals' risk-taking. A particular advantage of CFD trading is that it allows investors to make use of leverage, which provides us a pure measure of investors' willingness to take risks that is independent of the decision to purchase a particular stock. Leverage is a major catalyst of speculative trading, as it increases the scope of extreme returns, and enables investors to take larger positions than what they can afford with their own capital. We show that investors execute attention-driven trades with higher leverage, compared to their other trades, as well as those of other investors who are not alerted by attention triggers.

Green Deals Gain Steam - Kengelbach, Jens; Keienburg, Georg; Söllner, Tobias; Wang, Yiran; Sievers, Sönke; Friedmann, Daniel; Nielsen, Jesper (BCG M&A Report 2022)

Do Green Deals Create Value? - Kengelbach, Jens; Friedman, Daniel; Keienburg, Georg; Degen, Dominik; Söllner, Tobias; Wang, Yiran; Sievers, Sönke (BCG M&A Report 2022)

Information Leaks and Voluntary Disclosure - Ebert, Michael; Schäfer, Ulrich; Schneider, Georg Thomas

Does private firms’ disclosure affect public peers’ information environment? - Beyer, Bianca; Flagmeier, Vanessa; Kosi, Urska

Current developments in the European corporate bond market - Franke, Benedikt; Kosi, Urska; Stoczek, Pia
This paper introduces a novel database on the European corporate bond market to analyze the role of transparency regulation and recent developments in bond markets. We use data from the European Securities and Markets Authority (ESMA) to build a comprehensive database covering daily corporate bond listing information in Europe starting in 2018. We then analyze the different market segments of the European bond market along four key areas: (i) time and cross-sectional trends in bond listings; (ii) composition of firms on the market; (iii) firms’ financial reporting transparency; (iv) bond contract terms. Furthermore, we discuss the impact of recent economic events on these key areas.
Keywords: Transparency regulation; Corporate bond; European market

CSR Reporting under the Non-Financial Reporting Directive: Evidence from Non-publicly Listed Firms - Gulenko, Maryna; Kohlhase, Saskia; Kosi, Urska
We examine variation in mandatory CSR reporting practices based on a large sample of non-publicly listed savings banks in Germany. They do not have typical shareholders but rather are established by municipal trustees and can serve clients only in their distinct operating area. This setting permits us to identify demand for CSR information by their main stakeholder groups – municipal trustees and private and corporate clients. In this way, our analysis focuses on the double-materiality approach to CSR reporting. We find that demand for CSR information by supervisory board chairperson belonging to a left-wing or green party and the presence of more supervisory board members belonging to a left-wing or green party are associated with longer CSR reports and more disclosure on environmental, social, employee and human rights matters. In addition, competition for private clients and the sustainability orientation of corporate clients are associated with longer reports and more disclosure on environmental, employee and human rights matters. These findings suggest that savings banks’ CSR reports cater to their principal stakeholders’ demand for CSR information.
Keywords: Corporate social responsibility; Mandatory reporting; Non-publicly listed banks; Double materiality; Stakeholder groups; Political influence

Insolvcency Process in Germany and the insol database: A research Note - Ahlers, Theresa; Edossa, Fikir Worku; Uckert, Matthias; Kosi, Urska
This research note links the legal framework of the insolvency process of German firms to the information available in the newly-constructed insol database. In particular, the database contains information from documents published by German insolvency courts in period 2005- 2022. This research note first presents the insolvency process with steps and events of the process as determined by the Insolvency Law (InsO). Next, it classifies the documents to specific steps and events, and then presents their information content using textual analysis. Specifically, we identify target phrases via manual document checks and then create regular expressions for the target phrases. Classification of documents allows us to sketch most common paths that insolvent firms go through.
Keywords: insol database; insolvency process; Germany; court fillings

Arbitrage in the Market for Cryptocurrencies - Crépellière, Tommy; Pelster, Matthias; Zeisberger, Stefan (Journal of Financial Markets)

Steuerreformen: Investitionsstimulus oder bloß heiße Luft? Wann steuerliche Verlustrückträge der Wirtschaft helfen können - Sureth-Sloane, Caren

Income Shifting and Management Incentives - Ortmann, Regina; Schindler, Dirk

Tax Misperception and Its Effects on Decision Making - Literature Review and Behavioral Taxpayer Response Model - Blaufus, Kay; Chirvi, Malte; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren (European Accounting Review)
Previous accounting research shows that taxes affect decision making by individuals and firms. Most studies assume that agents have an accurate perception regarding their tax burden. However, there is a growing body of literature analyzing whether taxes are indeed perceived correctly. We review 128 studies on the measurement of tax misperception and its behavioral implications. The review reveals that many taxpayers have substantial tax misperceptions that lead to biased decision making. We develop a Behavioral Taxpayer Response Model on the impact of provided tax information on tax perception. Besides individual traits, characteristics of the tax information and the decision environment determine the extent of tax misperception. We discuss opportunities for future research and methodological limitations. While there is much evidence on tax misperception at the individual level, we hardly find any research at the firm level. Little is known about the real effects of managers’ tax misperception and on how tax information is strategically managed to impact stakeholders. This research gap is surprising as a large part of the accounting literature analyzes decision making and disclosure of firms. We recommend a mixed-method approach combining experiments, surveys, and archival data analyses to improve the knowledge on tax misperception and its consequences.

Pay for Tax Certainty? Advance Tax Rulings for Risky Investment under Multi-Dimensional Tax Uncertainty - Chen, An; Hieber, Peter; Sureth-Sloane, Caren

How Do Tax Technology and Controversy Expertise Affect Tax Disputes? - Dyck, Daniel; Lorenz, Johannes; Sureth-Sloane, Caren

Creating social and environmental value through integrated thinking: International evidence - Reimsbach, Daniel; Braam, Geert (Business Strategy and the Environment)
Abstract Integrated thinking (IT) is a managerial mindset increasingly discussed in the context of value creation. Through the lens of systems theory, this study examines how the degree to which IT is embedded in a firm's strategy and day‐to‐day business processes is associated with the firm's social and environmental value creation. Using a broad international dataset, we find strong evidence that our measure of IT is positively related to a firm's sustainability performance (SP), which we use to operationalize social and environmental value creation (or erosion). Our results also reveal that the increase in a firm's SP might come at the cost of a short‐term decrease in financial performance (FP). We find no indication, however, that IT induces a trade‐off between SP and long‐term FP. Integrated thinking appears to stipulate long‐term financial value creation instead. We further explore moderating factors within the organizational and institutional context of our sample firms and highlight implications for society, corporate practice, and policymaking.
Keywords: Management; Monitoring; Policy and Law; Strategy and Management; Geography; Planning and Development; Business and International Management

Semiparametric GARCH models with long memory applied to Value at Risk and Expected Shortfall - Letmathe, Sebastian; Feng, Yuanhua; Uhde, André (Journal of Risk)
In this paper new semiparametric generalized autoregressive conditional heteroscedasticity (GARCH) models with long memory are introduced. A multiplicative decomposition of the volatility into a conditional component and an unconditional component is assumed. The estimation of the latter is carried out by means of a data-driven local polynomial smoother. According to the revised recommendations by the Basel Committee on Banking Supervision to measure market risk in the banks’ trading books, these new semiparametric GARCH models are applied to obtain rolling one-step ahead forecasts for the value-at-risk and expected shortfall (ES) for market risk assets. Standard regulatory traffic-light tests and a newly introduced traffic-light test for the ES are carried out for all models. In addition, model performance is assessed via a recently introduced model selection criterion. The practical relevance of our proposal is demonstrated by a comparative study. Our results indicate that semiparametric long-memory GARCH models are a meaningful substitute for their conventional, parametric counterparts.
Keywords: long memory; generalized autoregressive conditional heteroscedasticity (GARCH) models; value-at-risk (VaR); expected shortfall (ES); traffic-light test; backtesting

Wait-and-see-ism as partial adoption of management practices: The rise and stall of integrated reporting - Endenich, Christoph; Hahn, Rüdiger; Reimsbach, Daniel; Wickert, Christopher (Strategic Organization)
Integrated reporting has widely been promoted as the next evolutionary step in corporate disclosure, which would soon replace traditional reporting practices. Embedded in a zeitgeist that favors sustainability, this outlook would suggest high integrated reporting adoption rates among reporting organizations. Our analysis of integrated reporting in Germany from 2008 to 2019 shows, however, that organizations approached integrated reporting with a wait-and-see mentality. This approach cannot be described adequately by the existing conceptualizations of (partial) practice adoption. We therefore develop the notion of wait-and-see-ism, defined as the deliberate and potentially long-lasting postponement of a decision to adopt a practice while its further development is monitored silently. We see limited, though continuous, efforts to prepare for the prospect of adopting the practice of integrated reporting quickly at a later stage. Wait-and-see-ism expands on prior work on partial adoption by emphasizing its temporal dimension. This adds an important yet undertheorized option that organizations can employ to respond to ambiguous institutional demands, thus explaining the stalling of promising management practices.
Keywords: Strategy and Management; Industrial relations; Education; Business and International Management

Losses Never Sleep - The Effect of Tax Loss Offset on Stock Market Returns during Economic Crises - Koch, Reinald; Holtmann, Svea; Giese, Henning

Lagerkapazitätsdimensionierung als betriebswirtschaftliches Entscheidungsproblem - Betz, Stefan (Aktuelle Fragestellungen zu Produktion, Controlling und Logistik)

Strategische Erfolgsplanung für Produktinnovationen - Betz, Stefan (Aktuelle Fragestellungen zu Produktion, Controlling und Logistik)

Tax Avoidance and Vertical Interlocks within Multinational Enterprises - Giese, Henning; Koch, Reinald; Gamm, Markus

Möglichkeiten und Grenzen der Messung, Kontrolle und Sicherung der Qualität logistischer Prozesse - Hrnjadovic, Damir (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Implikationen einer wertorientierten Unternehmensführung für Standortplanungsentscheidungen - Fiedler, Moritz (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Betriebliche Standortplanung international agierender Unternehmen - Osthoff, Lennart (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Kategorisierungsmöglichkeiten für die Erzeugung von Dienstleistungen - Opitz, Oliver (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Entscheidungsunterstützung durch das Controlling mittels Reporting Design - Faupel, Christian (Aktuelle Fragestellungen zu Produktion, Logistik und Controlling)

Aktuelle Fragestellungen zu Produktion, Controlling und Logistik

Transfer Pricing Rules for Intangibles: Implementation and Practical Challenges - Safaei, Reyhaneh

Changes in Transfer Pricing Regulations and Corporate Investment Decisions - Shabestari, Mehrzad Azmi; Safaei, Reyhaneh

Steuerliche Maßnahmen als Anreiz für Investitionen? - Sureth-Sloane, Caren (Die Presse)

Beste Bedingungen für junge Ökonominnen und Ökonomen? Neue Daten und Empfehlungen der AG Nachwuchs im Verein für Socialpolitik - Bayer, Christian; Engelmaier, Florian; Riphahn, Regina T.; Schmidt-Dengler, Philipp; Sondergeld, Virgina; Sureth-Sloane, Caren; von Wangenheim, Jonas; Weizsäcker, Georg

Steuerpolitische Perspektiven der neuen Legislaturperiode - Chancen und Herausforderungen - Sureth-Sloane, Caren (FinanzRundschau)

Wissenschaften in der Coronavirus-Pandemie - Erkenntnisse, Wissens- und Handlungslücken sowie Schlussfolgerungen für die Vorbereitung auf künftige Pandemien - Interdisziplinäre Kommission für Pandemieforschung, DFG; Sureth-Sloane, Caren

Wissenschaftliches Publizieren als Grundlage und Gestaltungsfeld der Wissenschaftsbewertung - Deutsche Forschungsgemeinschaft | AG Publikationswesen, (DFG); Sureth-Sloane, Caren
Academic publishing represents one of the core functions of scientific activity and thus of the research system. The Deutsche Forschungsgemeinschaft (DFG, German Research Foundation) is committed to the adequate communication of research results and the maintenance of a functioning publication system as a basic requirement of the research system. Ensuring that academic publishing serves foremost the purposes of publicising, quality review and documenting scientific findings should be an essential goal of responsible science administration and promotion. The position paper therefore analyses the central background of the current situation in scientific publishing, identifies challenges and points out possible fields of action. With this positioning, the DFG contributes to the further development of the publication system in a way that is appropriate for science and research.

Zusatzkosten der Besteuerung – Eine Analyse des steuerlichen Verwaltungsaufwands und der subjektiv wahrgenommenen Steuerbelastung (An Empirical Analysis of Firms’ Hidden Cost of Taxation) - Fochmann, Martin; Heinemann-Heile, Vanessa; Huber, Hans-Peter; Maiterth, Ralf; Sureth-Sloane, Caren
Keywords: General Earth and Planetary Sciences; General Environmental Science

Towards an Amended Arm's Length Principle - Tackling complexity and implementing destination rules in transfer pricing - Greil, Stefan; Overesch, Michael; Rohlfing-Bastian, Anna; Schreiber, Ulrich; Sureth-Sloane, Caren

Firms' Tax Rate Misperception: Measurement, Drivers, and Distortionary Effects - Fochmann, Martin; Heinemann-Heile, Vanessa; Huber, Hans-Peter; Sureth-Sloane, Caren

Chancen und Risiken eines Cooperative Compliance-Ansatzes für die deutsche Besteuerungspraxis von multinationalen Unternehmen – Erfahrungen verschiedener Länder und Eindrücke deutscher Unternehmensvertreter - Arbeitskreis Verrechnungspreise der Schmalenbach-Gesellschaft für Betriebswirtschaftslehre e.V., .; lead authors: Kreuzer, A; Maier, H; Martini, J. T.; Niemann, Rainer; Schachtebeck, Maite; Simons, Dirk; Stoltenberg, J; Sureth-Sloane, Caren (Internationales Steuerrecht)

Semiparametric GARCH models with long memory applied to Value at Risk and Expected Shortfall - Letmathe, Sebastian; Feng, Yuanhua; Uhde, André (Journal of Risk)
In this paper new semiparametric GARCH models with long memory are in- troduced. The estimation of the nonparametric scale function is carried out by an adapted version of the SEMIFAR algorithm (Beran et al., 2002). Recurring on the revised recommendations by the Basel Committee to measure market risk in the banks' trading books (Basel Committee on Banking Supervision, 2013), the semi- parametric GARCH models are applied to obtain rolling one-step ahead forecasts for the Value at Risk (VaR) and Expected Shortfall (ES) for market risk assets. In addition, standard regulatory traffic light tests (Basel Committee on Banking Supervision, 1996) and a newly introduced traffic light test for the ES are carried out for all models. The practical relevance of our proposal is demonstrated by a comparative study. Our results indicate that semiparametric long memory GARCH models are an attractive alternative to their conventional, parametric counterparts.
Keywords: Semiparametric; long memory; GARCH models; forecasting; Value at Risk; Expected Shortfall; traffic light test; Basel Committee on Banking Supervision

Dark triad managerial personality and financial reporting manipulation - Mutschmann, Martin; Hasso, Tim; Pelster, Matthias (Journal of Business Ethics)

Schmalenbach IMPULSE: Will etwas in Bewegung setzen - Asenkerschbaumer, Stefan; Sureth-Sloane, Caren

Option Implied Tax Rate Expectations - Eberbach, Jelena; Sureth-Sloane, Caren; Uhrig-Homburg, Marliese

Banks’ tax disclosure, financial secrecy, and tax haven heterogeneity - Eberhartinger, Eva; Speitmann, Raffael; Sureth-Sloane, Caren

Are Risk-based Tax Audit Strategies Rewarded? An Analysis of Corporate Tax Avoidance - Eberhartinger, Eva; Safaei, Reyhaneh; Sureth-Sloane, Caren; Wu, Yuchen

The Epidemiology of Tax Avoidance Narratives - Lorenz, Johannes; Diller, Markus; Sureth-Sloane, Caren
This study investigates the contagious nature of tax avoidance by examining how narratives affect tax avoiding behavior. We adapt the idea of narrative economics indicating that individuals' actions are stimulated by stories that spread within a society. We employ two types of infection models to theoretically investigate how tax avoidance schemes spread over time and vanish eventually consistent with patterns known from epidemiology. We find that general tax avoidance can persist even if its expected outcome is negative, while specific tax avoidance schemes might vanish even though their expected outcome is positive. We find empirical support for the predicted dissemination of narratives related to both general and specific tax avoidance schemes in google n-grams. Finally, we show that dissemination of specific tax avoidance schemes is attenuated by anti-narratives in (social) media. Our findings help to understand how tax avoidance spreads, under what conditions anti-avoidance measures can effectively curb tax avoidance and point towards the crucial role of transparency of enhanced enforcement by visible narratives.

Wiedereinführung der Vermögensteuer – eine ökonomische Analyse - Maiterth, Ralf; Sureth-Sloane, Caren (Steuer und Wirtschaft)
Die Diskussion über die adäquate Besteuerung von „Reichen“ bzw. „Superreichen“ hat durch die Schulden, die im Zusammenhang mit der Coronakrise zu finanzieren sind, neuen Schwung bekommen. Als ein Instrument der adäquaten „Reichenbesteuerung“ gilt eine jährliche Vermögensteuer. Den fiskalischen und verteilungspolitischen Argumenten zugunsten einer Vermögensbesteuerung stehen negative ökonomische Wirkungen entgegen. In diesem Beitrag soll zur Versachlichung der Debatte ein genauerer Blick auf die zu erwartenden Belastungswirkungen einer Vermögensteuer geworfen werden. Dabei wird deutlich, dass die (Wieder-)Einführung der Vermögensteuer nicht nur ungelöste Probleme der Bewertung von Sachvermögen mit sich bringt, sondern die Steuerbelastungswirkungen in der jetzigen Niedrigzinsphase zu erheblichen Nebenwirkungen führen. Berücksichtigt man eine Inflationsrate von 2 %, liegt die zur unternehmerischen Realkapitalerhaltung erforderliche Mindestrendite vor Steuern selbst bei einer lediglich 1 %igen Vermögensteuer mit 5,63 % weit über der Inflationsrate. Dies verdeutlicht, dass eine Vermögensteuer in Zeiten niedriger Renditen für Unternehmen eine zukunftssichernde Eigenkapitalerhaltung oder gar -bildung und zugleich wichtige Investitionen erheblich erschwert. Dies gilt auch für private Anlagen in Aktien und Immobilien. Darüber hinaus ist die Vermögensteuer auch in Verlustperioden zu bezahlen, so dass diese Steuer krisenverschärfend wirkt. Auch dies dürfte erhebliche negative Investitionswirkungen nach sich ziehen. Zudem ist damit zu rechnen, dass die Vermögensteuer zumindest in Teilen überwälzt wird, so dass letztlich auch Verbraucher, Arbeitnehmer und Mieter diese tragen werden. Diese und weitere Nebenwirkungen einer Vermögensteuer kommen in der Vermögensteuerdebatte oftmals zu kurz.

Two-period duopolies with forward markets - Cox, Caleb; Karam, Arzé; Pelster, Matthias (Review of Industrial Organization)
We experimentally consider a dynamic multi-period Cournot duopoly with a simultaneous option to manage financial risk and a real option to delay supply. The first option allows players to manage risk before uncertainty is realized, while the second allows managing risk after realization. In our setting, firms face a strategic dilemma: They must weigh the advantages of dealing with risk exposure against the disadvantages of higher competition. In theory, firms make strategic use of the hedging component, enhancing competition. Our experimental results support this theory, suggesting that hedging increases competition and negates duopoly profits even in a simultaneous setting.

Who participated in the GameStop frenzy? Evidence from brokerage accounts - Hasso, Tim; Müller, Daniel; Pelster, Matthias; Warkulat, Sonja (Finance Research Letters)
In January 2021, the GameStop stock was the epicenter of the first case of predatory trading initiated by retail investors. We use brokerage accounts to study who participated in this GameStop frenzy and how they performed. We investigate the extent to which investors’ personal and trading characteristics differ from the general population of retail investors. GameStop traders had a history of investing in speculative instruments, including stocks with lottery-like features. They were also more likely to close their positions before the peak of the bubble. At the onset of the frenzy, numerous retail investors also shorted GameStop. Overall, our results indicate that the GameStop frenzy was not a pure digital protest against Wall Street but speculative trading by a group of retail investors, in line with their prior high-risk trading behavior.
Keywords: Predatory Trading; Retail Investors; Trading Behavior

Inconsistent tax transfer prices: tax filings, audits, and double taxation - Lorenz, Johannes; Sureth-Sloane, Caren; Diller, Markus

Forschung und Entwicklung: Kriterien für die Aktivierung in der Unternehmenspraxis - Blankenfeldt, Maximilian; Müller, Jens; Weinrich, Arndt (Intangibles - Immaterielle Werte)

COVID-19 reporting and willingness to pay for leisure activities - Warkulat, Sonja; Krull, Sebastian; Ortmann, Regina; Klocke, Nina; Pelster, Matthias (Covid Economics)
The containment of COVID-19 critically hinges on individuals’ behavior. We investigate how individuals react to variations in COVID-19 reporting. Using a survey, we elicit individuals' perceived infection risk given various COVID-19 metrics (e.g., confirmed cases, reproduction rate, or case-fatality ratio). We proxy individuals' risk perception with their willingness to pay for the participation in everyday life and amusements events. We find that participants react to different COVID-19 metrics with varying sensitivity. We observe a saturation of sensitivity for several measures at critical limits used in the political discussion, making our results highly relevant for policy makers in their efforts to direct individuals to adhere to hygienic etiquette and social distancing guidelines.
Keywords: COVID-19 reporting; willingness to pay; willingness to accept

The Power and Peril of Precise vs. Round Health Message Interventions to Increase Stair-Use - Krull, Sebastian; Loschelder, David D.; Boecker, Lea (Frontiers in Psychology)

Tax avoidance through securitization - Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique hand-collected sample of 956 credit risk securitization transactions issued by 64 stock-listed European banks across the EU-13 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the impact of securitization on the issuing banks’ effective tax rates. Our analysis reveals that banks may reduce their tax expense through securitization via a direct and indirect channel suggesting that tax avoidance may be a further motive for banks to engage in the securitization business. These baseline findings remain robust under various robustness checks, especially when implementing structural equation models and controlling for a reverse causality between the banks’ tax burden and their incentive to securitize. Finally, various sensitivity analyses provide further important results and implications for tax policies, banking regulation and the ongoing process of revitalizing the European securitization market.
Keywords: Securitization; Credit risk transfer; Effective tax rates; European banking

Was treibt die Komplexität der Ertragsbesteuerung multinationaler Unternehmen? – Ergebnisse einer Befragung in der deutschen Finanzverwaltung - Bornemann, Tobias; Schipp, Adrian; Sureth-Sloane, Caren (Deutsches Steuerrecht)

Abweichende steuerliche Verrechnungspreise in der Steuererklärung oder als Ergebnis einer Betriebsprüfung zwischen verschiedenen Staaten - Lorenz, Johannes; Sureth-Sloane, Caren; Diller, Markus

Wie kompliziert darf eine Regel sein? - Sureth-Sloane, Caren; Simons, Dirk (Frankfurter Allgemeine Zeitung)

2020 Global MNC Tax Complexity Survey - Harst, Simon; Schanz, Deborah; Siegel, Felix; Sureth-Sloane, Caren

Wem nutzt Public Country-by-Country Reporting? - Lagarden, Martin; Schreiber, Ulrich; Simons, Dirk; Sureth-Sloane, Caren

Besteuerung und Rechtsformwahl, 8., aktualisierte und erweiterte Auflage - Maßbaum, Alexandra; Sureth-Sloane, Caren

Zur Komplexität des Steuersystems - Sureth-Sloane, Caren (Süddeutsche Zeitung)

Dark Triad Personality Traits and Selective Hedging - Pelster, Matthias; Hofmann, Annette; Klocke, Nina; Warkulat, Sonja (Journal of Business Ethics)
We study the relationship between risk managers' dark triad personality traits (Machiavellianism, narcissism, and psychopathy) and their selective hedging activities. Using a primary survey of 412 professional risk managers, we find that managers with dark personality traits are more likely to engage in selective hedging than those without. This effect is particularly pronounced for older, male, and less experienced risk managers. The effect is also stronger in smaller firms, less centralized risk management departments, and family-owned firms.

When do firms highlight their effective tax rate? - Flagmeier, Vanessa; Müller, Jens; Sureth-Sloane, Caren (Accounting and Business Research)
Keywords: Accounting; Finance

Development of a Strategic Controlling Concept - Fiedler, Moritz

Cost of Debt for Private Firms Revisited: Voluntary Audits as a Reflection of Risk - Ichev, Riste; Koren, Jernej; Kosi, Urska; Sitar Sustar, Katarina; Valentincic, Aljosa
This study examines the relation between voluntary audit and the cost of debt in private firms. We use a sample of 4,058 small private firms operating in the period 2006‐2017 that are not subject to mandatory audits. Firms decide for a voluntary audit of financial statements either because the economic setting in which they operate effectively forces them to do so (e.g., ownership complexity, export‐oriented supply chain, subsidiary status) or because firm fundamentals and/or financial reporting practices limit their access to financial debt, both reflected in earnings quality. We use these factors to model the decision for voluntary audit. In the outcome analyses, we find robust evidence that voluntary audits are associated with higher, rather than lower, interest rate by up to 3.0 percentage points. This effect is present regardless of the perceived audit quality (Big‐4 vs. non‐Big‐4), but is stronger for non‐Big‐4 audits where auditees have a stronger position relative to auditors. Audited firms’ earnings are less informative about future operating performance relative to unaudited counterparts. We conclude that voluntary audits facilitate access to financial debt for firms with higher risk that may otherwise have no access to this form of financing. The price paid is reflected in higher interest rates charged to firms with voluntary audits – firms with higher information and/or fundamental risk.
Keywords: private firms; voluntary audit; cost of debt; self‐selection bias; risk

COVID-19 Reporting and Willingness to Pay for Leisure Activities - Ortmann, Regina; Warkulat, Sonja; Krull, Sebastian; Klocke, Nina; Pelster, Matthias

Real effects of an international tax reform for MNEs - Ortmann, Regina; Simons, Dirk; Voeller, Dennis

Der Einfluss der Besteuerung auf Managementanreize und die Nutzung von Bonusbanken - Dyck, Daniel (Junior Management Science)

Editorial: Schmalenbach IMPULSE: Will etwas in Bewegung setzen - Asenkerschbaumer, Stefan; Sureth-Sloane, Caren (Schmalenbach IMPULSE)

CDS Investors’ Risk Perceptions of M&A Announcements - Hippert, Benjamin; Uhde, André
Merging a sample of 492 merger and acquisition (M&A) announcements from 284 acquiring firms across Europe and North America with data from 5-year single-name credit default swaps (CDSs) written on stock-listed acquiring firms between 2005 and 2018, the paper at hand empirically analyzes the CDS investors’ risk perceptions of M&A announcements using event study methodologies. As a baseline result, we provide evidence for significantly positive cumulative average abnormal CDS spread changes for both, European and North American acquirers suggesting that CDS investors perceive an increase in the acquiring firms’ credit risk exposures due to M&A announcements. Our baseline finding holds under several robustness checks, especially when controlling for the robustness of the empirical design. Moreover, results from a large variety of sensitivity analyses reveal a number of deal and firm characteristics that may explain why CDS investors from our sample expect an increase in the acquirers’ credit risk exposures due to forthcoming M&A transactions.
Keywords: credit default swaps; risk perception of CDS investors; mergers and acquisitions; event study